Deterritorialization in the context of cultural heritage and globalizing Msheireb downtown Doha - Al-Hammadi, Mariam Ibrahim (Frontiers in Sustainable Cities, 2023)
The State of Qatar has witnessed rapid urban activity and development in the decades since the discovery of oil, which has led to a large-scale change in the local cultural heritage and behavior of its residents. This uncontrolled rapid urbanization, along with the acceleration of globalization and modernity that has encompassed all areas, especially the city of Doha, has led to the deterioration and destruction of the downtown area of Msheireb. These transformations threaten the identity and local culture of Qatari society, affecting the place's sense of identity. The country's authorities have rushed to implement strategies and development plans aimed at redeveloping the old city center and improving the environment by creating innovative and inspiring living spaces that enable both locals and foreigners to communicate and integrate with one another to restore a sense of community. This study addresses the “Msheireb Downton Doha” project and the consequences of globalization. The study examines the concept of “deterritorialization” as a cultural condition that has pushed Msheireb Downtown Doha from modernity to postmodernism as an element of globalization. In this study, we will analyze the reconstruction of Msheireb, which helped to move the city toward cultural universality while simultaneously reducing regional borders. The study will analyze the extent to which this process succeeded or failed in preserving the spirit of the area's traditional architectural heritage and cultural identity in a manner that reflects the genuine sentiments and values of Qatari society.